2020
DOI: 10.1002/jpen.1842
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing International Approaches to Weaning Children From Tube Feeding: A Scoping Review

Abstract: Approaches to tube weaning enterally fed children and evaluating outcomes vary widely. This limits the utility of research for identifying both “what works” and successful implementation of research outcomes. We used a qualitative scoping review methodology to examine internationally published research. Our primary aim was to identify the main philosophies underpinning intervention design and the main outcome variables used to demonstrate success of existing programs. This information can be used to inform fut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 50 publications
(125 reference statements)
0
16
0
Order By: Relevance
“…There are multiple approaches that can be used to promote tube feeding weaning. A recent review investigating approaches to tube feeding weaning of pediatric patients identified three primary themes: child and family centered, biomedical treatment focused, or behavioral 37 . The child and family centered approach, as it sounds, heavily involves the caregiver in the weaning process and focuses on the child's self‐regulation with acceptance of oral food/beverages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are multiple approaches that can be used to promote tube feeding weaning. A recent review investigating approaches to tube feeding weaning of pediatric patients identified three primary themes: child and family centered, biomedical treatment focused, or behavioral 37 . The child and family centered approach, as it sounds, heavily involves the caregiver in the weaning process and focuses on the child's self‐regulation with acceptance of oral food/beverages.…”
Section: Discussionmentioning
confidence: 99%
“…The biomedical treatment focused approach utilizes medications, sensory stimulation and/or tube feeding adjustments to promote oral food/beverage intake. Alternatively, the behavioral strategy uses operant conditioning, such as altering the mealtime environment and the addition or removal of consequences in response to behavior, to address how the child responds to oral food/beverages 37 . There is no indication currently that one approach is preferable to another for promoting success of tube‐feeding weaning.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, their parents commonly experience great anxiety around feeding and weight gain 1. A number of programmes have been set up to address tube dependence worldwide 2. Most descriptions in the literature are of inpatient programmes, with feeds being withdrawn over a matter of days 2.…”
Section: Introductionmentioning
confidence: 99%
“…1 A number of programmes have been set up to address tube dependence worldwide. 2 Most descriptions in the literature are of inpatient programmes, with feeds being withdrawn over a matter of days. 2 There have been fewer descriptions of slower, outpatient tube weaning programmes, [3][4][5] although these will be more feasible in most settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation